2001
DOI: 10.1016/s0005-2736(01)00392-3
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of DNA in negatively charged liposomes and inhibition of bacterial gene expression with fluid liposome-encapsulated antisense oligonucleotides

Abstract: Antisense therapy for the treatment of bacterial infections is a very attractive alternative to overcome drug resistance problems. However, the penetration of antisense oligonucleotides into bacterial cells is a major huddle that has delayed research and application in this field. In the first part of this study, we defined efficient conditions to encapsulate plasmid DNA and antisense oligonucleotides in a fluid negatively charged liposome. Subsequently, we evaluated the potential of liposome-encapsulated anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…Thus, this strategy may raise the bar for infecting strains to develop resistance, potentially reducing future burdens of antimicrobial-resistant P. aeruginosa. Delivery of antisense oligonucleotides (AS-ODNs) via anionic liposomes has been successful in several bacterial species (72)(73)(74) and may provide a novel means for targeting sRNAs, such as PrrF and PrrH, to block virulence. Future work determining how each of the ⌬prrF1,2 mutant phenotypes contributes to P. aeruginosa virulence attenuation will be critical for the development of AS-ODN molecules that effectively block pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this strategy may raise the bar for infecting strains to develop resistance, potentially reducing future burdens of antimicrobial-resistant P. aeruginosa. Delivery of antisense oligonucleotides (AS-ODNs) via anionic liposomes has been successful in several bacterial species (72)(73)(74) and may provide a novel means for targeting sRNAs, such as PrrF and PrrH, to block virulence. Future work determining how each of the ⌬prrF1,2 mutant phenotypes contributes to P. aeruginosa virulence attenuation will be critical for the development of AS-ODN molecules that effectively block pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Anionic lipids (ALs) occur naturally in eukaryotic cell membranes, and DNA delivery systems based on ALs have recently been examined as an alternative to CLs because of their low cytotoxicity (11)(12)(13). ALs can be complexed with anionic DNA via interaction with multivalent cations such as Ca 2ϩ and have been shown to successfully transfer oligonucleotides.…”
mentioning
confidence: 99%
“…As a result, levels of encapsulation of 48.9% and 43.5% were found in the purified plasmid and oligonucleotide "antisense," respectively. 20 Other studies showed that, in dioctadecyldimethylammonium bromide bilayers, the preference of the monomeric amphotericin B was for the gel phase to be incorporated by 40%, compared to 23% in the fluid phase. 21 As in the DODAC/PHO-S liposomal formulation, the concentrations of PHO-S are not greater than the DODAC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In another liposomal formulation, researchers proposed the use of a negatively charged liposomal fluid to encapsulate an oligonucleotide "antisense" (anti-β-galactosidase), as well as the plasmid "pUC18." 20 In the study, the liposomes were formulated with synthetic phospholipids dipalmitoylphosphatidylcholine, and dimyristoyl phosphatidylglycerol in a molar ratio of 10:1, in the presence of a solution of a monovalent salt (NaCl, KCl, NaHCO 3 , or phosphate buffer), and the rate of encapsulation and activity "antisense" were measured by Escherichia coli CSH36. As a result, levels of encapsulation of 48.9% and 43.5% were found in the purified plasmid and oligonucleotide "antisense," respectively.…”
Section: Discussionmentioning
confidence: 99%